2017
DOI: 10.1007/s00248-017-0963-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Evolution and Dispersal Limitation Produce Biogeographic Patterns in Microcystis aeruginosa Populations of Lake Systems

Abstract: Molecular observations reveal substantial biogeographic patterns of cyanobacteria within systems of connected lakes. An important question is the relative role of environmental selection and neutral processes in the biogeography of these systems. Here we quantify the effect of genetic drift and dispersal limitation by simulating individual cyanobacteria cells using an agent-based model (ABM). In the model, cells grow (divide), die and migrate between lakes. Each cell has a full genome that is subject to neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…when the number of individuals in populations becomes relatively low (Crow & Kimura ), were extremely unlikely, because 3 × 10 5 cells were transferred in each step of the experiment, enough to avoid this. However, in scenarios with numerous small water bodies suffering salinization, neutral evolution and genetic drift events may occur, as has been recently described (Shirani & Hellweger ).…”
Section: Discussionmentioning
confidence: 87%
“…when the number of individuals in populations becomes relatively low (Crow & Kimura ), were extremely unlikely, because 3 × 10 5 cells were transferred in each step of the experiment, enough to avoid this. However, in scenarios with numerous small water bodies suffering salinization, neutral evolution and genetic drift events may occur, as has been recently described (Shirani & Hellweger ).…”
Section: Discussionmentioning
confidence: 87%
“…Given sufficient assumptions (e.g., uniform mutation rates, no recombination, constant and independent fitness effect of mutations) simple theories or equations can be developed and applied (e.g., to predict codon usage bias) [19]. For more complex scenarios, including multiple mechanisms and many sites (i.e., base pairs or genes), an alternative approach is to directly simulate a population of individual cells with whole genomes [20][21][22]. In this individual-or agent-based approach, single cells are simulated explicitly and the population-level properties (e.g., diversity and population size) emerge from the cumulative properties and behaviors of these low-level entities [23].…”
Section: Introductionmentioning
confidence: 99%
“…As dispersal limitation caused by geographic distance is one of the major mechanisms that maintain β-diversity of microbial communities (Eisenlord, Zak & Upchurch, 2012;Ni et al, 2014;Cao et al, 2016;Shirani & Hellweger, 2017), we analyzed the variation of the weighted UniFrac distances between the sampling sites with the geographic distances. Our results showed that the weighted UniFrac distances significantly increased with the increases of the geographic distances (Fig.…”
Section: Comparing the Rms Among Different Lakes Seasons And Sitesmentioning
confidence: 99%